Econometric and stochastic general equilibrium models for evaluation of economic policies. (1st April 2011) - Bhattarai, Keshab
Comparative analysis of economic structure and forecasts generated from simultaneous equation, VAR and autoregressive models based on quarterly series from 1966:1 to 2007:3 of UK to those from the stochastic general equilibrium models has provided insights into objective and subjective evaluation of macro economic impacts of public policies. Econometric estimates are used in formulation of stochastic dynamic general equilibrium models to generate time series of macro variables from stochastic general equilibrium models. Calibrating to ratios, variances, covariance and correlations econometric analyses and general equilibrium models are integrated and shown to be complementary not competitive techniques.